Molecular structure of nitrogen-linked methyltetrazole-saccharinates - Ismael, Amin (2014)
The molecular structures of nitrogen-linked 1- and 2-methyltetrazole-saccharinates, were investigated in the crystalline phase using X-ray crystallography and infrared and Raman spectroscopies, complemented by quantum chemical calculations performed at the DFT(B3LYP)/6-31++G(d,p) level of theory for the isolated molecules. In the neat crystalline solid (space group P 1, a = 6.9763 Å, b = 8.3097 Å, c = 10.0737 Å, a = 96.517 , b = 107.543 , c = 99.989 ; Z = 2), 1-methyltetrazole-saccharinate units assume the most stable configuration for the isolated molecule, (1H)-1-methytetrazole iminosaccharin tautomeric form (1MTIS), with the N@C spacer linking the two heterocycles. On the other hand, neat crystalline 2-methyl derivative units (space group P 1, a = 7.8010 Å, b = 8.6724 Å, c = 9.4984 Å, a = 114.083 , b = 107.823 , c = 93.080 ; Z = 2) exist in the (2H)-2-methytetrazole aminosaccharin tautomeric form (2MTAS), with the two heterocycles connected by an NH spacer. In both crystals, the structure consists of a packing of dimeric units, the dimers formed via hydrogen bonding involving either the NH group of the saccharyl system (1MTIS) or the spacer amine group (2MTAS). In the former, the hydrogen bond is bifurcated and the NH group acts as a donor both towards a neighbor molecule and an N atom of the tetrazole ring, forming an intramolecular hydrogen bond. The observed difference in the crystallographic basic units of the two compounds reveals the prevalence of the H-bond networks in determining the structural preferences of the tetrazole-saccharinates in the solid state. Such structural flexibility appears also to be of potential interest in the design of new ligands based on the tetrazole-saccharinate framework. The relative strengths of the H-bonds in the crystals of the two compounds were evaluated through inspection of their vibrational spectra and empirical correlations between spectroscopic data and the H-bond enthalpies and distances.